Phylogenetic exploration and haemato-biochemical significance of Anaplasma marginale infection in water buffalo (Bubalus bubalis) - Ganguly, Anita; Maharana, Biswa Ranjan; Kumar, Ankit (The Indian Journal of Animal Sciences, 2022)
During 2017-2020, a total of 8352 buffalo blood samples were screened microscopically for Anaplsma species and 104 positive samples were found. Later on same samples were confirmed positive using genomic DNA PCR technique. For efficiency of PCR technique, a total of 335 blood samples were randomly chosen. Microscopy revealed Anaplasma species in erythrocytes of 1.19% (4 samples) of the total blood samples (n=335). Initially PCR assay was standardized targeting 16S rRNA for detection of genus Anaplasma with expected amplicon size 781 bp. Thereafter, msp1 Î² gene was targeted for species level identification of Anaplasma (Anaplasma marginale) with expected amplicon size 407 bp. A total of fourteen samples out of 335 samples (4.17%) found positive by PCR. Randomly, two confirmed positive samples were sent for bidirectional sequencing. The sequencing results, submitted in GenBank(MW269530, MW269531), further confirm the Anaplasma marginale infection in buffalo. The study show higher specificity and sensitivity of PCR test above blood smear examination.Â Erythron of infected animals showed significantly low level of mean Hb, PCV, RBC count, MCH, MCHC and high level of mean MCV, indicating regenerative hypochromic macrocytic anaemia. Infected animals had a significantly low mean level of total protein, albumin and globulin and significantly high level of phosphorus, total bilirubin, direct and indirect bilirubin. The current study provides indication of the association between A. marginale infection and probable liver damage or hepatic fatty degeneration. Nevertheless advanced studies are warranted to explain the precise pathophysiological mechanism of this association.